2005
DOI: 10.1088/0031-9155/50/22/006
|View full text |Cite
|
Sign up to set email alerts
|

Resonance frequency of microbubbles in small blood vessels: a numerical study

Abstract: Microbubbles are currently used as ultrasound contrast agents. Their potential therapeutic applications are also under investigation. This work is designed to provide some insight into the mechanisms of energy absorption and deposition by a preformed gas bubble in the microvasculature to optimize its efficacy. In the linear regime, the most favourable condition for the transfer of energy from an ultrasonic field to a gas bubble occurs when the centre frequency of the ultrasonic field equals the resonance frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 39 publications
5
65
0
Order By: Relevance
“…They used a nonlinear lumped parameter model of the surrounding vessel and tissue as a boundary condition on the outer surface of the viscous, incompressible liquid, modeled with finite elements. Their predicted bubble natural frequency agrees with the one-dimensional cylindrical bubble model (Sassaroli and Hynynen, 2005) when the tube is rigid, however, the frequency increases as the vessel rigidity index, accounting for vessel thickness as well as stiffness, decreases.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…They used a nonlinear lumped parameter model of the surrounding vessel and tissue as a boundary condition on the outer surface of the viscous, incompressible liquid, modeled with finite elements. Their predicted bubble natural frequency agrees with the one-dimensional cylindrical bubble model (Sassaroli and Hynynen, 2005) when the tube is rigid, however, the frequency increases as the vessel rigidity index, accounting for vessel thickness as well as stiffness, decreases.…”
Section: Introductionsupporting
confidence: 56%
“…This spherically symmetric model can be used to approximate the behavior of a bubble in a vessel only if the bubble radius is much smaller than the vessel radius. For the opposite extreme, if the bubble radius is comparable to the vessel radius, a one-dimensional linear model of a cylindrical bubble can be used to approximate the behavior of the bubble in a rigid tube (Oguz and Prosperetti, 1998;Sassaroli and Hynynen, 2004;Sassaroli and Hynynen, 2005). Oguz and Prosperetti (1998) present simulation results using a boundary integral method for a bubble in a rigid tube that indicates that the large bubble approximation accurately predicts the bubble's natural frequency when the ratio of bubble radius to tube radius is greater than 0.2.…”
Section: Introductionmentioning
confidence: 95%
“…The vibration frequencies used in our study are several orders of magnitude lower than those that have been shown in animal experiments to induce gas bubble growth from micronuclei ( 1,35 ) and are substantially lower than the resonance frequency of microbubbles in blood vessels ( 34 ). Therefore, a purely resonance effect on micronuclei by these lowfrequency vibrations is unlikely.…”
Section: Discussionmentioning
confidence: 64%
“…1972) on the curve l, (5) The volume variance of the bubble is compensated by the vessel's deformation and after subtracting the scattered wave from the microbubble, the liquid at the end of the vessel can be considered to be undisturbed, as considered in Sassaroli and Hynynen (2005). Since the acoustic impedances of the microvessel, blood pool and surrounding tissue are similar, the boundary conditions at the microvessel ends are approximated as: (6) We found that a vessel length of 100μm is sufficiently long to obtain precise results within the typical computational interval of 5μs.…”
Section: Methodsmentioning
confidence: 99%